ChemInform Abstract: Synergy, Compatibility, and Innovation: Merging Lewis Acids with Stereoselective Enamine Catalysis. Issue 35 (September 2015) - Gualandi, Andrea; Mengozzi, Luca; Wilson, Claire M.; Cozzi, Pier Giorgio
Abstract Review: [73 refs.